Exploring The Educational Values of Character in As-Sulūk al-Asāsiyyah by Shaykh Muhammad Ba‘atiyah - Abdurrahman, Nanang; Syairozi, Ishak (Nizham Jurnal Studi Keislaman, 2025)
This study aims to explore the classical Islamic text As-Suluk al-Asasiyah to uncover its character education values relevant to Islamic religious education. The book was chosen due to its comprehensive content and limited prior academic investigation. The research seeks to identify character values, analyze their role in moral development, and evaluate their potential as a model for character education in both formal and informal Islamic institutions. A qualitative approach was employed using library research, with As-Suluk al-Asasiyah as the primary source, supported by secondary literature such as books, journals, and scholarly articles. The findings reveal four core categories of character values in the book: (1) al-imaniyah (faith-based values), which instill spiritual awareness; (2) al-jasadiyah (physical values), emphasizing hygiene and health ethics; (3) al-ubudiyah (worship values), promoting discipline in religious practices; and (4) al-ijtima’iyah (social values), fostering compassion and cooperation in society. These values are practical and align with the Islamic educational vision of forming a well-rounded, virtuous individual (insan kamil). Therefore, As-Suluk al-Asasiyah serves as a valuable reference for developing Islamic character education curricula, offering both contextual relevance and rootedness in Islamic moral traditions.